The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1155/2012/373025
|View full text |Cite
|
Sign up to set email alerts
|

Maxillomandibular Advancement in the Management of Obstructive Sleep Apnea

Abstract: Maxillomandibular advancement (MMA) is a surgical option for obstructive sleep apnea (OSA). MMA involves forward-fixing the maxilla and mandible approximately 10  mm via Le Fort I maxillary and sagittal split mandibular osteotomies. We retrospectively reviewed outcomes from 24 consecutive OSA patients who underwent MMA at our institution. MMA resulted in an 83% reduction in the group mean apnea-hypopnea index (AHI) per polysomnography an average of 6.7 months after surgery. Forty-two percent of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…[ Six out of 12 studies were not able to demonstrate any statistically significant predictor for MMA outcome [76][77][78][79][80][81]. The potentially predictive parameters presented in the remaining six studies were classified as described before (Table 10).…”
Section: Cephalometric Parameters With Oam In Situmentioning
confidence: 99%
“…[ Six out of 12 studies were not able to demonstrate any statistically significant predictor for MMA outcome [76][77][78][79][80][81]. The potentially predictive parameters presented in the remaining six studies were classified as described before (Table 10).…”
Section: Cephalometric Parameters With Oam In Situmentioning
confidence: 99%
“…Vigneron et al [ 11 ] performed maxillomandibular advancement surgery (MMA) on OSA patients and obtained a 50–80% reduction in AHI values after the surgery. Another study by Varghese et al [ 12 ] showed an 83% reduction in AHI value 6.7 months after the surgery. These results suggest that MMA can significantly reduce the AHI value, and therefore, it may be considered that maxillomandibular setback surgery could significantly increase the AHI value.…”
Section: Discussionmentioning
confidence: 98%
“…Selection of patients requires an extensive preoperative work up including UA imaging to enhance the success rates of the surgery [41,42] . Th ese procedures showed a non-inferior impact in terms of snoring, quality of life and EDS but it was not as good as CPAP in reducing AHI and the degree of oxygen desaturation [43][44][45] .…”
Section: Surgical Optionsmentioning
confidence: 99%